Bamboo vinegar as a sustainable botanical alternative for managing pineapple mealybugs, Dysmicoccus brevipes (Hemiptera: Pseudococcidae) - ROSAWANIS ROSLI; NURUL FATIHAH ABD LATIP; MOHAMMAD AZIZI ABDULLAH (Asian Journal of Agriculture, 2026)
Abstract. Rosli R, Abd Latip NF, Abdullah MA. 2026. Bamboo vinegar as a sustainable botanical alternative for managing pineapple mealybugs, Dysmicoccus brevipes (Hemiptera: Pseudococcidae). Asian J Agric 10 (1): g100133. https://doi.org/10.13057/asianjagric/g100133. The pineapple mealybug, Dysmicoccus brevipes, is a persistent pest that threatens pineapple production worldwide and is commonly managed using synthetic insecticides. However, intensive chemical use raises concerns related to environmental contamination, pest resistance, and residue accumulation. Botanical products such as Bamboo Vinegar (BV) have emerged as sustainable alternatives, yet evidence of their multifaceted bioactivity against mealybugs remains limited. This study evaluated the laboratory insecticidal and repellent efficacy of BV against D. brevipes using controlled bioassays. Mortality and survival were assessed over 24-120 h, while repellency was determined using an area-preference assay at 1 h and 6 h post-treatment. Kaplan-Meier survival analysis revealed a clear time-dependent reduction in mealybug survival, with median survival declining from 120.00±15.02 h to 72.00±11.30 h across BV concentrations. Differences among BV concentrations were modest, indicating consistent toxic effects within the tested range. In addition to mortality, BV induced consistent behavioral avoidance. Repulsion indices ranged from 0.26 to 0.52 across all concentrations, with 20% BV achieving the highest repellency (74.41±10.64%), exceeding that of white oil (60.80±19.58%). All treatments were classified within repellency Categories 3 and 4, reflecting moderate but reliable repellency. The primary novelty of this study lies in providing laboratory evidence that BV exhibits dual insecticidal-repellent activity against D. brevipes, combining lethal and sublethal effects within a single botanical input. While field validation and formulation optimisation are required, these results provide strong evidence that BV could be integrated into pineapple IPM programs as an eco-friendly tool to suppress mealybug populations and reduce reliance on synthetic insecticides.